PEMASYARAKATAN DAUR ULANG AIR LIMBAH UNTUK MENGANTISIPASI KELANGKAAN AIR AKIBAT PERUBAHAN IKLIM GLOBAL - Nugroho, Rudi (Jurnal Air Indonesia, 2014)
Climate change has impact on many sectors in the earth such as on the water resources sector. For example, the occurrence of floods and droughts in Indonesia that needs to be anticipated. In the Technology Needs Assessment document of the Republic of Indonesia, there are three priorities technology of the water sector to anticipate the climate change. One of the technologies is recycling domestic wastewater. The recycling of waste water can be done through two consecutive stages. First, wastewater treatment processes itself to produce the quality standard limits allowed to be discharged into the environment. Second is processing the treated wastewater till the product water can be used for particular purpose. There are many technologies can be used for water recycling process. Selection of technology depends on the type of waste water and product water quality targets. The utilization of recycled water in the community is still very little due to the barriers of technical and non-technical factors (social, economic, regulatory and others) which need to be anticipated along. Technical barrier include technology that is relatively more expensive to treat wastewater into products that can be utilized. While the non-technical barrier is many people are still reluctant to use the recycled water due to psychological factors. Therefore sosialization of waste water recycling to be expected can eliminate such barriers. Keywords: Water recycling, domestic waste, global climate change.